2018
DOI: 10.1029/2018ja025418
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Response to the April 2010 Electron Precipitation Event: Using WACCM and WACCM‐D With and Without Medium‐Energy Electrons

Abstract: Energetic electrons from the magnetosphere deposit their energy in the atmosphere and lead to production of nitric oxide (NO) in the mesosphere and lower thermosphere. We study the atmospheric NO response to a geomagnetic storm in April 2010 with WACCM (Whole Atmosphere Community Climate Model). Modeled NO is compared to observations by Solar Occultation For Ice Experiment/ Aeronomy of Ice in the Mesosphere at 72-82 ∘ S latitudes. We investigate the modeled NOs sensitivity to changes in energy and chemistry. T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 39 publications
1
41
0
Order By: Relevance
“…That even the baseline simulation shows a high bias would argue that too much auroral EEP and/or too-rapid descent in the MLT also contributes to the bias. An overestimate of auroral EEP is consistent with the WACCM results for the northern hemisphere winter of 2004 reported by Randall et al (2015), but inconsistent with the WACCM simulations of a geomagnetic storm in April 2010 reported by Smith-Johnsen et al (2018). The possibility that the bias is caused by too-rapid (or prolonged) descent is revisited below in the discussion of Figure 8.…”
Section: Journal Of Geophysical Research: Space Physicsmentioning
confidence: 66%
See 1 more Smart Citation
“…That even the baseline simulation shows a high bias would argue that too much auroral EEP and/or too-rapid descent in the MLT also contributes to the bias. An overestimate of auroral EEP is consistent with the WACCM results for the northern hemisphere winter of 2004 reported by Randall et al (2015), but inconsistent with the WACCM simulations of a geomagnetic storm in April 2010 reported by Smith-Johnsen et al (2018). The possibility that the bias is caused by too-rapid (or prolonged) descent is revisited below in the discussion of Figure 8.…”
Section: Journal Of Geophysical Research: Space Physicsmentioning
confidence: 66%
“…Water cluster chemistry can have a significant impact on odd nitrogen in the mesosphere, but is not included in the default model . As shown by Newnham et al (2018) and Smith-Johnsen et al (2018), SD-WACCM-D describes the mesosphere and lower thermosphere chemistry during geomagnetically active times more accurately than regular WACCM. For simplicity, for the remainder of the paper we refer to the model used as WACCM, but it should be understood that this is the specified dynamics version of WACCM4 with D-region chemistry.…”
Section: Numerical Simulations and Observationsmentioning
confidence: 94%
“…High-top models notoriously underestimate this effect, the cause being insufficient vertical transport and/or missing medium-energy electrons (e.g., Funke et al, 2017;Holt et al, 2013;Orsolini et al, 2017;Randall et al, 2015). Smith-Johnsen et al (2018) showed better agreement with observations when D region chemistry was added to the Whole Atmosphere Community Climate Model (WACCM) but the NO underestimate persisted between 90 and 110 km. Recent studies have shown that either constraining the model up to 90 km or assimilating mesospheric data improves the representation of the EPP IE Sassi et al, 2018;Siskind et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This layer in WACCM is placed at a higher altitude throughout almost the entire year, with a six kilometre difference as compared to SOFIE during winter. Auroral electron precipitation in WACCM has a characteristic energy of 2 keV, corresponding to a maximum energy deposition at an altitude of 110 km, but increasing this characteristic energy does not sufficiently lower the NO peak layer (Smith-Johnsen et al, 2017a).…”
mentioning
confidence: 99%